2013
DOI: 10.1093/carcin/bgt311
|View full text |Cite
|
Sign up to set email alerts
|

JWA suppresses tumor angiogenesis via Sp1-activated matrix metalloproteinase-2 and its prognostic significance in human gastric cancer

Abstract: JWA, a multifunctional microtubule-binding protein, plays an important role in regulating tumor metastasis via inhibition of matrix metalloproteinase-2 (MMP-2). Recent investigations suggest that MMP-2 is an angiogenesis-associated molecule. In this study, we provide novel evidence that JWA inhibits tumor angiogenesis in gastric cancer (GC). In two independent retrospective GC cohorts, we found that the expression of JWA was downregulated and that of MMP-2 was upregulated in GC tissues compared with the same i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
62
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(65 citation statements)
references
References 48 publications
3
62
0
Order By: Relevance
“…Regarding our finding of a greater decrease in MMP2 expression following YM155 treatment of EOMA cells than that noted following transfection with survivin siRNA, it is known that, like survivin, the MMP2 and MMP14 promoters also lack a typical TATA or CCAAT box, suggesting that Sp1 may be involved in regulating MMP2 and, possibly, MMP14 promoter activity (59,60), thus being consistent with YM155 also directly affecting MMP2 expression exclusive of its effects on survivin. Indeed, a recent study found that when Sp1 expression was reduced, MMP2 expression was reduced in human umbilical vein endothelial cells (59), consistent with the possibility that YM155 inhibition of at least these two proteins occurs via the same putative mechanism (33,34).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Regarding our finding of a greater decrease in MMP2 expression following YM155 treatment of EOMA cells than that noted following transfection with survivin siRNA, it is known that, like survivin, the MMP2 and MMP14 promoters also lack a typical TATA or CCAAT box, suggesting that Sp1 may be involved in regulating MMP2 and, possibly, MMP14 promoter activity (59,60), thus being consistent with YM155 also directly affecting MMP2 expression exclusive of its effects on survivin. Indeed, a recent study found that when Sp1 expression was reduced, MMP2 expression was reduced in human umbilical vein endothelial cells (59), consistent with the possibility that YM155 inhibition of at least these two proteins occurs via the same putative mechanism (33,34).…”
Section: Discussionsupporting
confidence: 83%
“…Indeed, a recent study found that when Sp1 expression was reduced, MMP2 expression was reduced in human umbilical vein endothelial cells (59), consistent with the possibility that YM155 inhibition of at least these two proteins occurs via the same putative mechanism (33,34).…”
Section: Discussionmentioning
confidence: 53%
“…These results were consistent with the findings of previous numerous researches on JWA gene (19). The present results indicated that the protein expression levels of PARP-1, vimentin and β-catenin were upregulated and E-cadherin was downregulated.…”
Section: Discussionsupporting
confidence: 93%
“…Sp1 was identified as a transcription factor by binding to the promoters of its target genes and has been postulated to play important roles in the regulation of multiple critical biological functions, including cell apoptosis [13] and growth [14], cycle progression [15], purine/pyrimidine synthesis [16], metabolism [17], angiogenesis [18],[19] and metastasis [20],[21]. Growing evidence demonstrated Sp1 is abnormally expressed in a variety of epithelial tumors originating from different tissues, including breast [22], thyroid [23], pancreas [24], stomach [25] and lung [26].…”
Section: Introductionmentioning
confidence: 99%